From crisis to stability in the Armenian power sector : lessons learned from Armenia's energy reform experience - Sargsyan, Gevorg, 1973- (World Bank working paper ;, 2006)
The last fifteen years have seen Armenia emerge from Soviet rule and a severe economic and energy crisis, both complicated by its newfound political surroundings. The last ten years have seen significant reform and progress in the power sector which, when compared to the progress made by its neighbors, is all the more remarkable. The benefits of reform have not been easily won, however, and Armenia's success is a tribute to its ability to learn from mistakes and persevere. A combination of improper planning and bad fortune forced the Government of Armenia to go through three separate tenders f.